2020
DOI: 10.1001/jamaoncol.2019.6276
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Chemotherapy With Hematopoietic Stem Cell Transplant in Patients With High-Risk Breast Cancer and 4 or More Involved Axillary Lymph Nodes

Abstract: IMPORTANCE Trials of adjuvant high-dose chemotherapy (HDCT) have failed to show a survival benefit in unselected patients with breast cancer, but long-term follow-up is lacking. OBJECTIVE To determine 20-year efficacy and safety outcomes of a large trial of adjuvant HDCT vs conventional-dose chemotherapy (CDCT) for patients with stage III breast cancer. DESIGN, SETTING, AND PARTICIPANTS This secondary analysis used data from a randomized phase 3 multicenter clinical trial of 885 women younger than 56 years wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…The application of valrubicin has been reported to have benefits for the treatment of skin tumors [59], and it also has a certain effect on some bladder cancers [60]. Epirubicin has a certain effect on the combined treatment of breast cancer, and there is certain evidence in many clinical trials [61, 62]. Enoxacin, as an antibacterial drug, may be a useful option for cervical cancer treatment [63].…”
Section: Discussionmentioning
confidence: 99%
“…The application of valrubicin has been reported to have benefits for the treatment of skin tumors [59], and it also has a certain effect on some bladder cancers [60]. Epirubicin has a certain effect on the combined treatment of breast cancer, and there is certain evidence in many clinical trials [61, 62]. Enoxacin, as an antibacterial drug, may be a useful option for cervical cancer treatment [63].…”
Section: Discussionmentioning
confidence: 99%
“…There is no conclusive data on high dose chemotherapy and stem cell long term benefits compared to standard therapy ( Chen B. B. et al, 2016 ; Steenbruggen et al, 2020 ). While the combination of chemotherapy and stem cell therapy is hopeful as a treatment for cancer, there is conflicting literature at this time to unequivocally predict its efficacy in humans, as it can be dependent on type of chemotherapy, type of stem cells, and type of cancer ( Somlo et al, 1994 ; VanderWalde et al, 2012 ; Qian et al, 2017 ).…”
Section: Caveats For Combining Stem Cell Therapy With Chemotherapymentioning
confidence: 99%
“…High dose chemotherapy in combination with stem cells for breast cancer patients show long-term event-free survival, but an overall survival benefit is not significant ( Berry et al, 2011 ). Likewise, high dose adjuvant chemotherapy with autologous hematopoietic stem cells has no significant overall survival value compared to control ( Steenbruggen et al, 2020 ). However, there is evidence in breast cancers that involve at least ten axillary lymph nodes, HER2 negative breast cancer, and triple negative breast cancer ( Steenbruggen et al, 2020 ).…”
Section: Caveats For Combining Stem Cell Therapy With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…A promising treatment to improve overall survival is high-dose chemotherapy with autologous stem cell rescue (HDCT). Unfortunately, HDCT has only shown limited clinical bene t in high-risk breast cancer, at the expense of considerable toxicity during the rst year after diagnosis, and long-term toxicity comparable to conventional chemotherapy [4,5,6]. For example, pre-planned analyses of Dutch and American randomized controlled trials showed that HDCT improved 5-year relapse-free survival up to 10% for breast cancer patients with 10 or more positive lymph nodes [7,8].…”
Section: Introductionmentioning
confidence: 99%